Documentação química, toxicidade e atividades biológicas de Chamaecrista duckeana I & B e Chamaecrista ensiformis I & B - Lima, Daniele Rodrigues de (2022)
This work presents the results obtained from the unpublished study of two plants of the genus Chamaecrista, native to the Brazilian flora and which present rare studies on chemical composition and biological potential. Chemical documentation of the metabolic profile of Chamaecrista duckeana I&B and Chamaecrista ensiformis I&B extracts was performed using the UHPLC-MS technique (ultra performance liquid chromatography coupled to mass spectrometry). The chemical profiles are dominated by flavonoids, but with the presence of anthraquinones, chalcones, coumarins, chromones, phenylpropanoids and sesquiterpenes. Thirty-four (34) compounds were identified that are being reported for the first time in both species. The antioxidant activity of the extracts of leaves, stems and fruits of C. duckeana was performed using an in vitro assay, by scavenging the free radical DPPH and in the evaluation of the cytotoxic activity of the extracts, the MTT assay was used, and IC50 values ​​were determined against the cell lines HL60 and RAJI cell lines. The extracts showed antioxidant potential, and the activity of the stem extract was superior to the standard BHT. In the cytotoxic assay, only the HL60 cell line (leukemia) showed growth inhibition greater than 80%. The stem extract showed the most expressive cytotoxicity with IC50 of 137.3 (104.6-180.1) and 106.8 (96.52-118.3) μmol L-1 for HL60 and RAJI, respectively. Extracts from leaves and flowers of C. ensiformis were investigated for their toxicity against adult Zebrafish (Danio rerio). Antioxidant activity was performed using the DPPH and ABTS assays and the antiacetylcholinesterase potential was performed using the Ellman method. Cytotoxicity was tested using the MTT method. The data obtained revealed that the extracts were not toxic against adult Zebrafish (Danio rerio) up to 96 h of analysis. The leaf extracts showed good antioxidant activity with an IC50 value of 5.516 ± 0.027 µg mL-1 in the ABTS method. The extract of C. ensiformis flowers inhibited the enzyme acetycholinesterase (AChE), with an inhibition halo of 0.8 cm in diameter and showed a significant cytotoxic effect against cell lines HL60 and RAJI with IC50 of 88.76 and 90.23 µg mL-1, respectively. The present work presents a comprehensive and unprecedented knowledge about the species C. duckeana and C. ensiformis, rich in bioactive secondary metabolites with cytotoxic activity.